PENGARUH FISCAL STRESS DAN PERUBAHAN ANGGARAN SiLPA TERHADAP PERUBAHAN ANGGARAN BELANJA MODAL PEMERINTAH PROVINSI - Zaizafun, Rena; Jalaluddin, Jalaluddin; Batara, Gamal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
The purpose of this study is to examine the impact of fiscal stress and changes in the previous year's budget surplus on changes in the capital expenditure budget. This quantitative study focuses on all provincial governments in Indonesia. Using purposive sampling with the criterion of having a budget deficit, 69 observations were selected as samples. The study applied a multiple linear regression analysis approach to analyze secondary data, which was processed using IBM SPSS statistics. The results indicate that changes in the capital expenditure budget are influenced by fiscal stress and changes in the previous years budget surplus. Furthermore, fiscal stress has certain implications for budgetary decision-making, potentially affecting government spending priorities. These findings highlight the importance of financial management strategies in mitigating the effects of fiscal stress and the previous years budget surplus in ensuring optimal capital expenditure allocation. The study contributes to understanding how fiscal conditions and fund management shape government budgeting policies.